Evolving concepts in intracranial pressure monitoring - from traditional monitoring to precision medicine - Mathur, Rohan; Cheng, Lin; Lim, Josiah; Azad, Tej D.; Dziedzic, Peter; Belkin, Eleanor; Joseph, Ivanna; Bhende, Bhagyashri; Yellapantula, Sudha; Potu, Niteesh; Lefebvre, Austen; Shah, Vishank; et al. (Neurotherapeutics, 2025)
A wide range of acute brain injuries, including both traumatic and non-traumatic causes, can result in elevated intracranial pressure (ICP), which in turn can cause further secondary injury to the brain, initiating a vicious cascade of propagating injury. Elevated ICP is therefore a neurological injury that requires intensive monitoring and time-sensitive interventions. Patients at high risk for developing elevated ICP undergo placement of invasive ICP monitors including external ventricular drains, intraparenchymal ICP monitors, and lumbar drains. These monitors all generate an ICP waveform, but each has its own unique caveats in monitoring and accuracy. Current ICP monitoring and management clinical guidelines focus on the mean ICP derived from the ICP waveform, with standard thresholds of treating ICP greater than 20 ​mmHg or 22 ​mmHg applied broadly to a wide range of patients. However, this one-size fits all approach has been criticized and there is a need to develop personalized, evidence-based and possibly multi-factorial precision-medicine based approaches to the problem. This paper provides historical and physiological context to the problem of elevated ICP, provides an overview of the challenges of the current paradigm of ICP management strategies, and discusses advances in ICP waveform analysis, emerging non-invasive ICP monitoring techniques, and applications of machine learning to create predictive algorithms. [Display omitted]